Inquiry into mathematics teacher education - Arbaugh, Fran; Taylor, P. Mark (AMTE professional book series ;, 2008)
(Orginally published in 2008) The 14 chapters in this monograph provide support for mathematics teacher educators in both their Practical Knowledge and their Professional Knowledge. Individually, these articles provide insights into advancing our thinking about professional development, teacher preparation, and program development. Collectively, they have the potential to help the field of mathematics teacher education move forward in framing effective practices in mathematics teacher education and developing a focused, cohesive research agenda. ATME's Monograph 5, therefore, is a superb resource for mathematics teacher education.